2023
DOI: 10.1038/s41416-023-02260-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk and mortality of testicular cancer in patients with neurodevelopmental or other psychiatric disorders

Abstract: Background Both testicular germ cell tumours (TGCT) and neurodevelopmental disorders are associated with urogenital malformations. Few studies have investigated the association between psychiatric disorders and TGCT. We investigated whether history of any psychiatric or neurodevelopmental disorder is associated with increased risk or mortality of TGCT. Method This is a nested case–control study including 6166 TGCT patients diagnosed during 1992–2014, indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Possible underlying mechanisms have also been suggested 28 , 29 . Risk of testicular cancer was increased among patients with NDDs or other psychiatric disorders which is observed in a case-control study 30 .…”
Section: Introductionmentioning
confidence: 69%
“…Possible underlying mechanisms have also been suggested 28 , 29 . Risk of testicular cancer was increased among patients with NDDs or other psychiatric disorders which is observed in a case-control study 30 .…”
Section: Introductionmentioning
confidence: 69%
“…For instance, a retrospective cohort study carried out in Taiwan reported that ADHD was associated with an increased risk of colorectal cancer (adjusted Hazard Ratio = 3.458, 95% CI = 1.640–7.293, p < 0.001) [ 77 ]. Furthermore, a history of a neurodevelopmental disorder (ADHD, autism spectrum disorder, and intellectual disabilities) was associated with an increased risk of seminoma) in a nested case-control study (OR: 1.54; 1.09–2.19 [ 78 ]. Moreover, ADHD shows substantial genetic correlations with nonpsychiatric conditions, including lung cancer [ 79 ].…”
Section: Speer Allergic Tension-fatigue Syndrome (Satfs) Re-visitedmentioning
confidence: 99%